Inhibition of long chain fatty acyl-CoA synthetase (ACSL) and ischemia reperfusion injury - Prior, Allan M.; Zhang, Man; Blakeman, Nina; Datta, Palika; Pham, Hung; Chen, Qian; Young, Lindon H.; Weis, Margaret T.; Hua, Duy H. (My University, 2014)
Various triacsin C analogs, containing different alkenyl chains and carboxylic acid bioisoteres including 4-aminobenzoic acid, isothiazolidine dioxide, hydroxylamine, hydroxytriazene, and oxadiazolidine dione, were synthesized and their inhibitions of long chain fatty acyl-CoA synthetase (ACSL) were examined. Two methods, a cell-based assay of ACSL activity and an in situ [¹⁴C]-palmitate incorporation into extractable lipids were used to study the inhibition. Using an in vivo leukocyte recruitment inhibition protocol, the translocation of one or more cell adhesion molecules from the cytoplasm to the plasma membrane on either the endothelium or leukocyte or both was inhibited by inhibitors 1, 9, and triacsin C. The results suggest that inhibition of ACSL may attenuate the vascular inflammatory component associated with ischemia reperfusion injury and lead to a decrease of infarct expansion.
Keywords: Hydroxytriazene; Ischemia reperfusion injury; Long chain fatty acyl-CoA synthetase (ACSL); Inhibitors; Oxadiazolidine dione; Triacsin C